Application of polyanionic cellulose as multi-effect functional material in aqueous zinc ion battery

By using polyanionic cellulose (PAC) in aqueous zinc ion batteries for negative electrode interface modification, electrolyte addition and separator modification, the problems of uneven dendrites growth and corrosion are solved, the stability and mechanical properties of the battery are improved, and multi-scenario optimization and improvement are achieved.

CN120432682APending Publication Date: 2025-08-05SUN YAT SEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510560503.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2025-08-05

AI Technical Summary

Technical Problem

Existing aqueous zinc ion batteries face problems such as uneven dendrite growth, zinc corrosion and hydrogen evolution side reactions, resulting in device short circuits, zinc loss and Coulomb efficiency reduction, making it difficult to achieve multi-scene and multi-angle optimization and improvement.

Method used

Polyanionic cellulose (PAC) is used as a multi-effect functional material for negative electrode interface modification, electrolyte additives and diaphragm modification, and dendrite deposition is regulated through various channels to enhance the mechanical properties of electrode interfaces and diaphragms.

Benefits of technology

Effectively inhibit dendrites and corrosion, improve battery stability and life, improve the overall mechanical performance of electrolytes and separators, realize multi-scene optimization and improvement, and meet the low-cost requirements of the green development strategy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120432682A_ABST
    Figure CN120432682A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of zinc ion batteries, and particularly relates to application of polyanionic cellulose as a multi-effect functional material in an aqueous zinc ion battery. The invention provides a multi-effect functional material for an aqueous zinc ion battery, namely polyanionic cellulose (PAC), which can be applied to diaphragm modification, electrode interface modification and electrolyte additives in multiple scenes, not only can effectively inhibit dendritic crystal and corrosion phenomena, but also can remarkably improve the overall mechanical properties of an electrolyte and a diaphragm, so that the service life of the electrolyte and the diaphragm is prolonged. And multi-scene and multi-function optimization and improvement of the water-based zinc ion battery are realized. Compared with the traditional material, the multi-effect functional material selected by the invention breaks through the limitation in the aspects of modification approach and function optimization. On the basis of keeping low cost and environment-friendly characteristics, the material can greatly improve the performance of water-based zinc ion batteries (ZIBs), and is expected to provide powerful support for wide popularization and application of the ZIBs in the fields of industrial production, practical application, daily life and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of zinc ion batteries, and particularly relates to the application of polyanionic cellulose as a multi-effect functional material in aqueous zinc ion batteries. Background Art

[0002] With the rapid development of industrialization, traditional fossil fuels are no longer able to meet the ever-increasing energy demand, and the global energy structure has entered a critical period of transformation. Driven by the rise of clean energy sources such as wind and solar power and the increasing popularity of electric vehicles, rechargeable batteries have experienced rapid development. Today, as we prioritize ecological development and pursue a green, low-carbon development path, and unwaveringly implement the new energy security strategy, energy transformation and development are continuously reaching new heights.

[0003] Lithium-ion batteries (LIBs) have become the main choice for rechargeable battery applications due to their excellent rate performance and cycle life, and have been successfully commercialized. However, the practical problems faced by LIBs cannot be ignored: (1) The chemical properties of lithium are active, and the organic electrolyte is flammable and toxic, resulting in the risk of combustion, explosion and toxic leakage of LIBs during production and use. There are significant thermal runaway and toxicity risks, which pose a serious threat to the safety of production and terminal applications. (2) The global distribution of lithium resources is highly uneven (for example, the "Lithium Triangle" in South America accounts for more than 60%), and the lithium resource reserves in some regions are relatively low, resulting in restrictions on the energy storage industry chain. (3) The explosive growth in demand for LIBs has caused a shortage of raw materials (such as fluctuations in the price of lithium carbonate), increased manufacturing costs, and made it difficult for them to adapt to the long-term needs of grid-level energy storage in terms of economic efficiency and supply scale. Therefore, finding alternatives to LIBs has also become a new research hotspot.

[0004] Among them, zinc-ion batteries (ZIBs), as a new type of energy storage device, have great potential in addressing the problems faced by LIBs, such as poor safety and high cost, and are very likely to become an alternative to LIBs. ZIBs have the following advantages: (1) High safety ZIBs can use aqueous electrolytes, avoiding the safety hazards and biological toxicity of organic electrolytes after leakage; (2) Excellent performance Zinc metal has a low redox potential (-0.76V vs SHE) and an excellent theoretical capacity (5855mAh·cm -3 or 820mAh·g -1 ); (3) Rich reserves Zinc has abundant reserves (75 parts per million in the earth's crust) and high element abundance (about 300 times higher than lithium). At the same time, my country's zinc metal resources are extremely rich, and ZIBs have high strategic security.

[0005] Although aqueous electrolytes have significant advantages such as high ionic conductivity, low cost, and eco-friendliness, their practical application still faces technical challenges, especially the problem of uniform zinc deposition. Non-uniform deposition can easily induce dendrite growth, leading to device short circuit or zinc loss ("dead zinc" phenomenon). In addition, zinc is prone to side reactions such as corrosion and hydrogen evolution in aqueous electrolytes, which not only consumes limited zinc, but also leads to reduced Coulombic efficiency and shortened cycle life. The above phenomena seriously limit its practical application and become the biggest obstacle to the commercialization of ZIBs.

[0006] At present, in order to overcome the problems of dendrites, hydrogen evolution and corrosion in ZIBs, functional materials are usually introduced to modify the various components of the battery. The corresponding solutions are mainly divided into three categories: surface modification of zinc negative electrode, composition regulation of electrolyte and composite design of battery separator. However, in actual operation, the use of a single and limited modification idea is often difficult to fully cope with the diverse challenges faced by aqueous batteries, and many problems will be encountered: (1) The application of existing functional materials is often limited to a single component, and it is difficult to achieve "multi-scenario" application under electrodes, separators and electrolytes. (2) Existing improvement technologies are often limited to single problems in dendrites, hydrogen evolution and corrosion, and it is difficult to achieve "multi-angle" optimization of zinc ion batteries at the same time. (3) The existing selection of modified materials often has practical problems such as high cost and difficulty in recycling, which is difficult to fit in with the existing green development strategy. Therefore, it is necessary to develop a ZIBs functional material that can be applied in multiple scenarios and has multiple functions. Summary of the Invention

[0007] In order to overcome the deficiencies of the above-mentioned prior art, the present invention provides a multi-functional material for aqueous zinc-ion batteries, namely polyanionic cellulose (PAC), which can be applied to the optimization and modification of multiple components such as the negative electrode, electrolyte and separator. It can not only maintain the economic and environmental advantages of aqueous zinc-ion batteries, but also significantly improve battery performance and achieve multi-effect regulation of dendrites, hydrogen evolution and corrosion, thus developing a new approach for the high-value utilization of cellulose in the field of green and sustainable new energy storage device materials.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] The first aspect of the present invention provides the application of PAC in aqueous zinc ion batteries, wherein the application method includes at least one of negative electrode interface modification, electrolyte additive, and diaphragm modification.

[0010] PAC is a water-soluble cellulose ether derivative made by chemically modifying natural cellulose. It has good hydrophilicity, film-forming properties and electrical insulation. Compared with other cellulose derivatives, it has outstanding advantages such as higher degree of substitution and more uniform and stable distribution of substituents. The present invention has found that: PAC has excellent ion regulation ability, and its carboxyl group is conducive to promoting Zn 2+ By accelerating the desolvation process and homogenizing the ion flow, PAC can effectively control dendrite deposition on the electrode surfaces of ZIBs and inhibit corrosion through various approaches, including electrode interface modification, electrolyte additives, and separator composites. Furthermore, it exhibits a favorable composite strengthening effect on materials such as separators, solid-state or quasi-solid-state electrolytes, effectively improving their overall mechanical properties and enhancing the original material's resistance to dendrite penetration. Therefore, PAC can simultaneously meet the application needs of aqueous zinc-ion batteries in anode interface modification, electrolyte additives, composite electrolytes, and separator modification.

[0011] The present invention applies PAC to multiple scenarios such as negative electrode interface modification, electrolyte additives, composite electrolytes and diaphragm modification, fully utilizing its polyhydroxyl and polycarboxyl characteristics, and provides a new green and "global" approach to the modification of novel aqueous zinc-ion batteries.

[0012] The basic method of the technical solution of the present invention is: to apply PAC in multiple scenarios to negative electrode interface modification, electrolyte additives, composite electrolytes and diaphragm modification, etc. Specifically including: ① in the negative electrode interface modification application, a PAC modification layer is constructed on the surface of the zinc negative electrode by surface coating, electrostatic adsorption, self-assembly, spraying, electrophoresis or electrochemical deposition; ② in the electrolyte additive application, PAC is used as an additive component and directly dissolved into the electrolyte to adjust the overall ion flow distribution of the electrolyte; ③ in the solid or quasi-solid electrolyte application, PAC is used as a functional component and is simply composited or cross-linked with other electrolyte matrices (cross-linked and coupled with a cross-linking agent or electrolyte matrix through chemical reaction); ④ in the diaphragm modification application, PAC is used as a functional component and is simply composited or cross-linked with the diaphragm (cross-linked and coupled with a cross-linking agent or electrolyte matrix through chemical reaction).

[0013] The multi-scenario application of PAC is specifically described in the aqueous zinc-ion batteries described in the second to fifth aspects:

[0014] A second aspect of the present invention provides an aqueous zinc ion battery, comprising a positive electrode, a negative electrode, and an aqueous zinc ion solid or quasi-solid electrolyte, wherein the aqueous zinc ion solid or quasi-solid electrolyte is a solid or quasi-solid composite electrolyte containing PAC.

[0015] Preferably, the aqueous zinc ion solid or quasi-solid electrolyte is a composite electrolyte prepared by compounding PAC with a solid or quasi-solid electrolyte matrix; specific compounding methods include simple compounding or cross-linking compounding using a cross-linking agent; wherein, simple compounding refers to direct physical compounding of PAC with the electrolyte matrix without chemical reaction during the process, and specific processes include surface coating, solution casting, electrospinning, impregnation or self-assembly; cross-linking compounding is to cause a cross-linking chemical reaction between PAC and the cross-linking agent or electrolyte matrix.

[0016] More preferably, the composite solid or quasi-solid electrolyte matrix includes one or more inorganic electrolytes such as oxides and zinc salt crystals (such as ZnPS3 crystals), or one or more organic electrolytes such as sodium alginate, cellulose (such as microcrystalline cellulose, microfibrillated cellulose (MFC) or bacterial cellulose), polyvinyl alcohol, chitosan and carbonate.

[0017] More preferably, the crosslinking agent used in the composite crosslinking includes one or more of inorganic metal salts (such as calcium silicate, magnesium silicate or borax), organic peroxides (such as benzoyl peroxide), aldehydes (such as glutaraldehyde, urea-formaldehyde or formaldehyde) and acids (such as citric acid, tannic acid or polyacrylic acid) crosslinking agents.

[0018] More preferably, the proportion of PAC in the solid or quasi-solid composite electrolyte is 1-50 wt%.

[0019] Furthermore, the proportion of PAC in the solid or quasi-solid composite electrolyte is 5-30 wt%.

[0020] The third aspect of the present invention further provides an aqueous zinc ion battery, which includes a positive electrode, a negative electrode, a diaphragm and an aqueous zinc ion electrolyte, and the diaphragm is a PAC-modified diaphragm.

[0021] Preferably, the preparation method of the PAC modified membrane is: dissolving PAC in water to prepare a modified solution, or dissolving PAC and a cross-linking agent in water to prepare a modified solution; then using the obtained modified solution to soak, spray, self-assemble or surface-coat the membrane, and then heating and drying.

[0022] Preferably, the concentration of PAC in the modified solution is 0.1-30 g / L.

[0023] Furthermore, the concentration of PAC in the modified solution is 1-20 g / L.

[0024] More preferably, the PAC modified membrane may be made of one or more of glass fiber, cellulose (such as natural cellulose or regenerated cellulose), chitosan, chitin, lignin and polymer (such as polyacrylamide, polypropylene, polyether ketone or polysulfone ether).

[0025] More preferably, the cross-linking agent includes one or more of salts (such as calcium silicate, magnesium silicate or borax), organic peroxides (such as benzoyl peroxide), aldehydes (such as glutaraldehyde, urea-formaldehyde or formaldehyde) and acids (such as citric acid, tannic acid or polyacrylic acid) cross-linking agents.

[0026] More preferably, the mass ratio of the PAC to the cross-linking agent is 1:10 to 10:1.

[0027] The fourth aspect of the present invention also provides an aqueous zinc ion battery, which includes a positive electrode, a negative electrode, a separator and an aqueous zinc ion electrolyte, wherein the aqueous zinc ion electrolyte is a zinc ion electrolyte with PAC as an additive.

[0028] Preferably, the concentration of PAC in the zinc ion electrolyte is 0.005-5 g / L, and the concentration of zinc ions in the electrolyte is 0.01-5 M.

[0029] More preferably, the electrolyte can also be used in combination with one or more common electrolyte additives such as ammonium salts (such as ammonium chloride or diethylammonium hydrochloride), inorganic metal salts (such as magnesium sulfate or stannous chloride), alcohols (such as ethylene glycol, propylene glycol or polyethylene glycol), ethers (such as crown ether or ethylene glycol dimethyl ether), esters (such as propylene carbonate), acids (such as glutamic acid or citric acid) and sugars (such as glucose, sucrose or maltose).

[0030] The fifth aspect of the present invention also provides an aqueous zinc ion battery, which includes a positive electrode, a negative electrode, a separator and an aqueous zinc ion electrolyte, and the negative electrode is a PAC modified electrode.

[0031] Preferably, the preparation method of the PAC modified electrode is to construct a PAC modified layer on the surface of the zinc negative electrode by surface coating, electrostatic adsorption, self-assembly, spraying, electrophoresis or electrochemical deposition, etc. The modified layer thickness is 1 to 25 μm.

[0032] Preferably, the negative electrode that can be modified with PAC includes one or more of zinc sheet, zinc plate, zinc powder, zinc foam and zinc alloy materials.

[0033] More preferably, in the various aqueous zinc ion batteries described above, the zinc salt is selected from one or more combinations of zinc sulfate, zinc acetate, zinc chloride, zinc nitrate, zinc fluoride, zinc hexafluoride, zinc trifluoromethanesulfonate, zinc bis(trifluoromethanesulfonyl imide), and zinc tetrafluoroborate. The concentration of the zinc salt is 0.01-5M.

[0034] Preferably, in the various aqueous zinc ion batteries involved above, the separator is selected from one or more of glass fiber, cellulose (such as natural cellulose or regenerated cellulose), chitosan, chitin, lignin and polymer (such as polyacrylamide, polypropylene, polyether ketone or polysulfone ether).

[0035] Preferably, in the various aqueous zinc ion batteries involved above, the positive electrode is one or more of vanadium-based compounds, manganese-based compounds, disulfides, metal-based spinel materials, Prussian blue derivatives, conductive polymers, polyanion compounds, carbonyl compounds, triphenylamine derivatives, nitrooxyethers and imine compounds.

[0036] Preferably, in the various aqueous zinc ion batteries mentioned above, the negative electrode comprises one or more of zinc sheet, zinc plate, zinc powder, zinc foam and zinc alloy material.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] The multi-effect functional material (PAC) provided by the present invention has powerful performance and can be applied to negative electrode interface modification, electrolyte additives, composite electrolytes and diaphragm modification in multiple scenarios. It can not only effectively inhibit dendrites and corrosion phenomena, but also significantly improve the overall mechanical properties of the electrolyte and the diaphragm, thereby achieving multi-scenario and multi-functional optimization and improvement of aqueous zinc-ion batteries. It is worth mentioning that PAC materials, as derivatives of cellulose products, naturally have outstanding advantages such as low pollution, low cost and green environmental protection. Compared with traditional materials, the multi-effect functional material (PAC) selected by the present invention has broken through the limitations in modification approaches and optimization functions. On the basis of maintaining low cost and environmental protection characteristics, this material can greatly improve the performance of aqueous zinc-ion batteries. A series of aqueous zinc-ion battery optimized electrodes, electrolyte additives, composite electrolytes (simple composite or cross-linked composite) and modified diaphragms (simple composite or cross-linked composite) prepared based on this material are expected to provide support for the wide application of aqueous zinc-ion batteries in industrial production, practical applications and daily life.

[0039] Specifically, the present invention has the following advantages:

[0040] (1) This multi-functional material (PAC) can be applied in multiple scenarios in negative electrode interface modification, electrolyte additives, composite electrolytes and diaphragm modification, achieving multi-site improvement of aqueous zinc-ion batteries.

[0041] (2) This multifunctional material (PAC) can simultaneously effectively regulate the dendrite and corrosion problems of aqueous zinc-ion batteries, significantly improving battery life and stability.

[0042] (3) This multifunctional material (PAC) is widely available and green and renewable, and has both excellent cost-effectiveness and excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 1 is a comparison chart of hydrogen evolution in the electrolyte of Example 1 and Comparative Example 1.

[0044] Figure 2 2 is a comparison chart of hydrogen evolution in the electrolyte of Example 2 and Comparative Example 1.

[0045] Figure 3 3 is a comparison chart of hydrogen evolution in the electrolyte of Example 3 and Comparative Example 1.

[0046] Figure 4 The figure is a comparison chart of the tensile strength, puncture strength and stress-strain curve during the tensile process in Example 5 and Comparative Example 2.

[0047] Figure 5 This is a comparison chart of the full battery rate test in Example 5 and Comparative Example 2.

[0048] Figure 6 The following is a comparison diagram of the scanning electron microscope (SEM) image and the super depth of field microscope image in Example 6 and Comparative Example 2.

[0049] Figure 7 2 is a comparison chart of the symmetrical battery cycle performance in Example 6 and Comparative Example 2.

[0050] Figure 8 This is a comparison chart of the zinc ion migration numbers of the symmetrical batteries in Example 6 and Comparative Example 2.

[0051] Figure 9 The figure is a comparison diagram of the stress-strain curve and puncture strength of the stretching process in Example 7 and Comparative Example 3.

[0052] Figure 10 It is a comparison chart of the puncture strength in Example 8 and Comparative Example 3.

[0053] Figure 11 This is a comparison chart of the puncture strength in Example 9 and Comparative Example 3.

[0054] Figure 12 This is a comparison chart of the rate performance of the symmetrical batteries in Examples 7 and 10 and Comparative Example 3.

[0055] Figure 13 This is a comparison chart of the symmetrical battery cycle performance in Example 11 and Comparative Example 4. DETAILED DESCRIPTION

[0056] The following is a further description of specific embodiments of the present invention. It should be noted that the description of these embodiments is intended to facilitate understanding of the present invention and does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below may be combined with each other as long as they do not conflict with each other.

[0057] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.

[0058] Example 1: Aqueous zinc ion symmetric battery based on modified electrodes

[0059] (1) Take 0.5 g of PAC and add water to 100 mL. After magnetic stirring at room temperature for 20 min, a 5 g / L PAC solution is obtained.

[0060] (2) In order to eliminate the influence of zinc ion deposition on the observation of hydrogen evolution reaction, Na2SO4-based electrolyte was used instead of ZnSO4-based electrolyte. 14.204 g of Na2SO4 was added to the above PAC solution. After magnetic stirring for 10 min at room temperature, a composite modified solution of 1 M Na2SO4 + 5 g / L PAC was obtained.

[0061] (3) The prepared PAC composite modified solution was coated on the surface of a clean zinc electrode and dried at 50°C for 1 h to obtain a PAC-Zn electrode. The thickness of the PAC modified layer on the electrode surface was about 20 μm.

[0062] (4) Take 14.204 g of Na2SO4 and add water to make up to 100 mL to obtain a 1 M Na2SO4 solution.

[0063] (5) In order to eliminate the influence of zinc ion deposition on the observation of hydrogen evolution reaction, a Zn||Zn symmetrical cell was assembled using 1M Na2SO4 obtained in step (4) as the electrolyte. -2 Unidirectional constant current charging was carried out at a surface current density of , and hydrogen evolution on the negative electrode surface was observed at 0, 5, 10 and 15 min respectively.

[0064] Example 2: Aqueous zinc ion symmetric battery based on composite electrolyte

[0065] (1) Take 0.5 mg of PAC and add water to 100 mL. After magnetic stirring at room temperature for 20 min, a 5 mg / L PAC solution is obtained.

[0066] (2) In order to eliminate the influence of zinc ion deposition on the observation of hydrogen evolution reaction, Na2SO4-based electrolyte was used instead of ZnSO4-based electrolyte. 14.204 g of Na2SO4 was added to the above PAC solution and magnetically stirred at room temperature for 10 min to obtain a Na2SO4-based composite electrolyte of 1 M Na2SO4 + 5 mg / L PAC.

[0067] (3) The Zn||Zn symmetrical battery was assembled using the above-mentioned Na2SO4-based composite electrolyte. -2 Unidirectional constant current charging was carried out at a surface current density of , and hydrogen evolution on the negative electrode surface was observed at 0, 5, 10 and 15 min respectively.

[0068] Example 3: Aqueous zinc ion symmetric battery based on composite electrolyte

[0069] (1) Take 0.5 g of PAC and add water to 100 mL. After magnetic stirring at room temperature for 20 min, a 5 g / L PAC solution is obtained.

[0070] (2) In order to eliminate the influence of zinc ion deposition on the observation of hydrogen evolution reaction, Na2SO4-based electrolyte was used instead of ZnSO4-based electrolyte. 14.204 g of Na2SO4 was added to the above PAC solution and magnetically stirred at room temperature for 10 min to obtain a Na2SO4-based composite electrolyte of 1 M Na2SO4 + 5 g / L PAC.

[0071] (3) Using Na2SO4-based composite electrolyte to assemble Zn||Zn symmetric battery. -2 The battery was charged in a unidirectional constant current manner at a surface current density of 100 nm, and the hydrogen evolution on the negative electrode surface was observed at 0, 1, 2 and 3 min, respectively.

[0072] Example 4: Composite quasi-solid electrolyte based on 5% PAC

[0073] (1) Weigh 0.0143 g of PAC and 13.5420 g of 2 wt% MFC dispersion in a beaker, add 35 mL of deionized water, and stir magnetically for 10 min to obtain an MFC-5% PAC mixed solution.

[0074] (2) Transfer the above solution into a culture dish and dry it at 50℃.

[0075] (3) After drying and molding, the MFC-5% PAC composite quasi-solid electrolyte is obtained.

[0076] (4) The above film samples were cut into standard dog-bone specimens and subjected to tensile testing on a universal specimen machine.

[0077] Example 5: Composite quasi-solid electrolyte based on 30% PAC and its Zn||PANI@CNT full battery

[0078] (1) Weigh 0.0855 g of PAC and 9.9783 g of 2 wt% MFC dispersion in a beaker, add 35 mL of deionized water, and stir magnetically for 10 min to obtain an MFC-30% PAC mixed solution.

[0079] (2) Transfer the above solution into a culture dish and dry it at 50℃.

[0080] (3) After drying and molding, the MFC-30% PAC composite quasi-solid electrolyte is obtained.

[0081] (4) The above film samples were cut into standard dog-bone specimens and subjected to tensile testing on a universal specimen machine; they were cut into standard disc specimens and subjected to puncture testing on a universal specimen machine.

[0082] (5) Take 57.512 g of ZnSO4·6H2O and add water to make the volume to 100 mL to obtain a 2M ZnSO4 aqueous zinc ion electrolyte.

[0083] (6) The electrolyte membrane sample of step (3) was cut into discs with a diameter of 16 mm and immersed in the 2M ZnSO4 electrolyte prepared in step (5) for 24 h.

[0084] (7) Prepare a solution by dissolving 17.755 g of Na₂SO₄, 6.8 mL of H₂SO₄ (98.3 wt%), and 4.56 mL of aniline in 400 mL of deionized water. The solution was then magnetically stirred for 10 min. Subsequently, deionized water was added to bring the volume to 500 mL to prepare a 2 M aniline solution.

[0085] (8) Using the aniline solution obtained above as the electrolyte, cut several 1×2 cm 2 The multi-walled carbon nanotube film (Carbon Nanotube, CNT) was used as the current collector, the platinum sheet was used as the working electrode, and the saturated calomel electrode was used as the reference electrode. Cyclic voltammetry was used for electrodeposition in a three-electrode system with a voltage range of 0-0.8 V, a scan rate of 60 mV / s, and 30 scan cycles.

[0086] (9) The electrode obtained after the above electroplating was rinsed with ultrapure water and placed in an oven and dried at 50°C for 30 min to obtain a PANI@CNT positive electrode.

[0087] (10) After removing surface moisture from the composite quasi-solid electrolyte membrane sample of step (6), place it together with the PANI@CNT positive electrode of step (9) in a button cell to assemble a Zn||PANI@CNT full battery (Note: when using a solid or quasi-solid electrolyte, no diaphragm is required).

[0088] (11) The battery of step (10) was heated at 0.5, 0.8, 1, 2 and 4 A·g -1 The cyclic charge and discharge test was carried out at a surface current density of .

[0089] Example 6: Composite quasi-solid electrolyte reinforced with a cross-linker and aqueous zinc ion symmetric battery thereof

[0090] (1) Weigh 0.0855 g of PAC and 9.9783 g of 2 wt% MFC dispersion, add 35 mL of deionized water, and stir magnetically for 10 min to obtain an MFC-30% PAC mixed solution.

[0091] (2) Weigh 0.0309 g of citric acid (CA, cross-linking agent) and dissolve it in the above solution. Heat it in a water bath at 50° C. and stir it magnetically until it is completely dissolved to obtain an MFC-30% PAC-CA mixed solution.

[0092] (3) Transfer the above solution into a culture dish and dry it at 50°C.

[0093] (4) After drying and molding, the MFC-30% PAC-CA composite quasi-solid electrolyte is obtained.

[0094] (5) Take 57.512 g of ZnSO4·6H2O and add water to make the volume to 100 mL to obtain a 2M ZnSO4 aqueous zinc ion electrolyte.

[0095] (6) The electrolyte membrane sample of step (4) was cut into discs with a diameter of 16 mm and immersed in the 2M ZnSO4 electrolyte prepared in step (5) for 24 h.

[0096] (7) Take out the composite quasi-solid electrolyte membrane sample, remove the surface moisture and place it in a button cell to assemble a Zn||Zn symmetrical battery (Note: when using solid or quasi-solid electrolyte, no separator is required).

[0097] (8) The battery of step (7) was charged at 2 mA·cm -2 The surface current density and 1 mAh·cm -2 After 100 cycles at the surface specific capacity, the zinc electrode was taken out, washed and dried, and characterized by SEM and ultra-depth of field microscopy.

[0098] (9) The battery of step (7) is tested using an electrochemical workstation to calculate the zinc ion electromigration number.

[0099] (10) The battery of step (7) was charged at 4 mA·cm -2 The surface current density and 2mAh·cm -2 The cyclic charge and discharge test was carried out at the surface specific capacity.

[0100] Example 7: Modified glass fiber separator based on simple PAC composite and aqueous zinc ion symmetric battery

[0101] (1) 0.1 g of PAC was added to 20 mL of deionized water and magnetically stirred at room temperature for 20 min to obtain a 5 g / L PAC solution.

[0102] (2) Transfer the above solution to a culture dish and heat it in a water bath at 50°C for 2 h with magnetic stirring during the heating process.

[0103] (3) Immerse the glass fiber membrane in the 5 g / L PAC solution heated in the water bath and take it out after soaking for 2 minutes.

[0104] (4) The impregnated glass fiber membrane was placed at 50°C and dried for 6 hours to obtain a 5 g / L PAC-modified glass fiber membrane.

[0105] (5) The above film samples were cut into standard dog-bone specimens and subjected to tensile testing on a universal specimen machine; they were cut into standard disc specimens and subjected to puncture testing on a universal specimen machine.

[0106] (6) Take 57.512 g of ZnSO4·6H2O and add water to make the volume to 100 mL to obtain a 2M ZnSO4 aqueous zinc ion electrolyte.

[0107] (7) Using the modified glass fiber separator of step (4), 200 mL of the electrolyte of step (6) was added dropwise to assemble a Zn||Zn symmetrical battery. -2 The surface current density and 1 mAh·cm -2 The cyclic charge and discharge test was carried out at the surface specific capacity.

[0108] Example 8: Modified glass fiber diaphragm based on 1g / L PAC cross-linked composite

[0109] (1) 0.02 g of PAC was added to 20 mL of deionized water and magnetically stirred at room temperature for 20 min to obtain a 1 g / L PAC solution.

[0110] (2) Take 0.04 g of glutaric dialdehyde (GA) solution (50 wt%) as a cross-linking agent and add it to the above PAC solution. After magnetic stirring at room temperature for 10 minutes, a 1 g / L PAC+GA solution (the mass ratio of PAC to GA is 1:1) is obtained.

[0111] (3) The obtained 1 g / LPAC+GA solution was transferred to a culture dish and heated in a water bath at 50°C for 2 h with magnetic stirring during the heating process.

[0112] (4) Immerse the glass fiber membrane in a 1 g / L PAC-GA solution heated in a water bath and take it out after soaking for 2 minutes.

[0113] (5) The soaked glass fiber membrane was placed at 50°C and dried for 6 hours to obtain a 1 g / LPAC+GA modified glass fiber membrane.

[0114] (6) Cut the above film sample into a standard disc sample and perform a puncture test on a universal sample machine.

[0115] Example 9: Modified glass fiber diaphragm based on 20g / L PAC cross-linked composite

[0116] (1) 0.4 g of PAC was added to 20 mL of deionized water and magnetically stirred at room temperature for 20 min to obtain a 20 g / L PAC solution.

[0117] (2) 0.8 g of GA solution (50 wt%) was taken as a cross-linking agent and added to the above PAC solution. After magnetic stirring at room temperature for 10 min, a 20 g / LPAC+GA solution (the mass ratio of PAC to GA was 1:1) was obtained.

[0118] (3) The obtained 20 g / L PAC+GA solution was transferred to a culture dish and heated in a water bath at 50°C for 2 h with magnetic stirring during the heating process.

[0119] (4) Immerse the glass fiber membrane in a 20 g / L PAC-GA solution heated in a water bath and take it out after soaking for 2 minutes.

[0120] (5) The soaked glass fiber membrane was placed at 50°C and dried for 6 h to obtain a 20 g / LPAC+GA modified glass fiber membrane.

[0121] (6) Cut the above film sample into a standard disc sample and perform a puncture test on a universal sample machine.

[0122] Example 10: Modified glass fiber separator reinforced with a crosslinker and aqueous zinc ion symmetric battery thereof

[0123] (1) 0.1 g of PAC was added to 20 mL of deionized water and magnetically stirred at room temperature for 20 min to obtain a 5 g / L PAC solution.

[0124] (2) 0.2 g of GA solution (50 wt%) was taken as a cross-linking agent and added to the above PAC solution. After magnetic stirring at room temperature for 10 min, a 5 g / LPAC+GA solution (the mass ratio of PAC to GA was 1:1) was obtained.

[0125] (3) The obtained 5 g / LPAC+GA solution was transferred to a culture dish and heated in a water bath at 50°C for 2 h with magnetic stirring during the heating process.

[0126] (4) Immerse the glass fiber membrane in a 5 g / L PAC+GA solution heated in a water bath and take it out after soaking for 2 minutes.

[0127] (5) The soaked glass fiber membrane was placed at 50°C and dried for 6 hours to obtain a 5g / LPAC+GA modified glass fiber membrane.

[0128] (6) Take 57.512 g of ZnSO4·6H2O and add water to make the volume to 100 mL to obtain a 2M ZnSO4 aqueous zinc ion electrolyte.

[0129] (7) Using the modified glass fiber separator of step (5), 200 mL of the electrolyte of step (6) was added dropwise to assemble a Zn||Zn symmetrical battery. -2 The surface current density and 1 mAh·cm -2 The cyclic charge and discharge test was carried out at the surface specific capacity.

[0130] Example 11: Modified cellulose membrane reinforced with a cross-linking agent and aqueous zinc ion symmetric battery thereof

[0131] (1) 0.1 g of PAC was added to 20 mL of deionized water and magnetically stirred at room temperature for 20 min to obtain a 5 g / L PAC solution.

[0132] (2) 0.2 g of GA solution (50 wt%) was added to the above PAC solution, and the mixture was magnetically stirred at room temperature for 10 min to obtain a 5 g / LPAC+GA solution (the mass ratio of PAC to GA was 1:1).

[0133] (3) The obtained 5 g / LPAC+GA solution was transferred to a culture dish and heated in a water bath at 50°C for 2 h with magnetic stirring during the heating process.

[0134] (4) Immerse the cellulose membrane in the 5 g / L PAC+GA solution heated in the water bath and take it out after soaking for 2 minutes.

[0135] (5) The impregnated cellulose membrane was dried at 50°C for 6 h to obtain a 5 g / LPAC+GA modified cellulose membrane.

[0136] (6) Take 57.512 g of ZnSO4·6H2O and add water to make the volume to 100 mL to obtain a 2M ZnSO4 aqueous zinc ion electrolyte.

[0137] (7) Using the modified cellulose membrane of step (5), 200 mL of the electrolyte of step (6) was added dropwise to assemble a Zn||Zn symmetrical battery. -2 The areal current density and 0.5 mAh·cm -2 Comparative Example 1: Aqueous zinc ion symmetric battery based on additive-free electrolyte and unmodified electrode

[0138] (1) In order to eliminate the influence of zinc ion deposition on the observation of hydrogen evolution reaction, Na2SO4-based electrolyte was used instead of ZnSO4-based electrolyte. 14.204 g of Na2SO4 was taken and added with water to make the volume 100 mL. After magnetic stirring at room temperature for 10 min, 1 M Na2SO4 electrolyte was obtained.

[0139] (2) Using 1M Na2SO4 electrolyte to assemble Zn||Zn symmetric battery. -2 At the surface current density of 1.5 Å, the surface hydrogen evolution was observed at 0, 5, 10 and 15 min respectively.

[0140] (3) Using 1M Na2SO4 electrolyte to assemble Zn||Zn symmetric battery. -2 At the surface current density of 1.5 Å, the surface hydrogen evolution was observed at 0, 1, 2 and 3 min respectively.

[0141] Comparative Example 2: Quasi-solid electrolyte based on pure MFC and its aqueous zinc ion symmetric battery and Zn||PANI@CNT full battery

[0142] (1) Weigh 13.5468 g of 2 wt% MFC dispersion into a beaker, add 35 mL of deionized water, and stir magnetically for 10 min to obtain an MFC solution.

[0143] (2) Transfer the above solution into a culture dish and dry it at 50℃.

[0144] (3) After drying and molding, pure MFC quasi-solid electrolyte is obtained.

[0145] (4) The above film samples were cut into standard dog-bone specimens and subjected to tensile testing on a universal specimen machine; they were cut into standard disc specimens and subjected to puncture testing on a universal specimen machine.

[0146] (5) Take 57.512 g of ZnSO4·6H2O and add water to make the volume to 100 mL to obtain a 2M ZnSO4 aqueous zinc ion electrolyte.

[0147] (6) The electrolyte membrane sample prepared in step (3) was cut into discs with a diameter of 16 mm and immersed in the prepared 2M ZnSO4 electrolyte for 24 h.

[0148] (7) Prepare a solution by dissolving 17.755 g of Na₂SO₄, 6.8 mL of H₂SO₄ (98.3 wt%), and 4.56 mL of aniline in 400 mL of deionized water. The solution was then magnetically stirred for 10 min. Subsequently, deionized water was added to bring the volume to 500 mL to prepare a 2 M aniline solution.

[0149] (8) Using the aniline solution obtained above as the electrolyte, cut several 1×2 cm 2 The CNT was used as the current collector, the platinum sheet was used as the working electrode, and the saturated calomel electrode was used as the reference electrode. Cyclic voltammetry was used for electrodeposition in a three-electrode system with a voltage range of 0 to 0.8 V, a scan rate of 60 mV / s, and 30 scan cycles.

[0150] (9) The electrode obtained after the above electroplating was rinsed with ultrapure water and placed in an oven and dried at 50°C for 30 min to obtain a PANI@CNT positive electrode.

[0151] (10) After removing surface moisture from the composite quasi-solid electrolyte membrane sample of step (6), place it together with the PANI@CNT positive electrode of step (9) in a button cell to assemble a Zn||PANI@CNT full battery (Note: when using a solid or quasi-solid electrolyte, no diaphragm is required).

[0152] (11) The battery of step (10) was heated at 0.5, 0.8, 1, 2 and 4 A·g -1 The cyclic charge and discharge test was carried out at a surface current density of .

[0153] (12) The electrolyte membrane sample in step (6) is placed in a button cell after removing surface moisture, and a Zn||Zn symmetrical cell is assembled.

[0154] (13) The battery of step (12) was charged at 2 mA·cm -2 The surface current density and 1 mAh·cm -2After 100 cycles at the surface specific capacity, the zinc electrode was taken out, washed and dried, and characterized by SEM and ultra-depth of field microscopy.

[0155] (14) The battery of step (12) is tested using an electrochemical workstation to calculate the zinc ion electromigration number.

[0156] (15) The battery of step (12) was charged at 4 mA·cm -2 The surface current density and 2mAh·cm -2 The cyclic charge and discharge test was carried out at the surface specific capacity.

[0157] Comparative Example 3: Aqueous zinc ion symmetric battery based on unmodified glass fiber separator

[0158] (1) Take 57.512 g of ZnSO4·6H2O and add water to make the volume to 100 mL to obtain a 2M ZnSO4 aqueous zinc ion electrolyte.

[0159] (2) The glass fiber diaphragm is cut into a standard dog-bone specimen and subjected to a tensile test on a universal specimen machine; it is cut into a standard disc specimen and subjected to a puncture test on a universal specimen machine.

[0160] (3) Using the glass fiber separator and the electrolyte in step (1) to assemble a Zn||Zn symmetrical battery, and respectively at 1, 2, 4, 6, 8, and 10 mA·cm -2 The surface current density and 1 mAh·cm -2 The cyclic charge and discharge test was carried out at the surface specific capacity.

[0161] Comparative Example 4: Aqueous zinc ion symmetric battery based on unmodified cellulose membrane

[0162] (1) Take 57.512 g of ZnSO4·6H2O and add water to make the volume to 100 mL to obtain a 2M ZnSO4 aqueous zinc ion electrolyte.

[0163] (2) A Zn||Zn symmetrical battery was assembled using the cellulose separator and the above electrolyte. -2 The areal current density and 0.5 mAh·cm -2 The cyclic charge and discharge test was carried out at the surface specific capacity.

[0164] The test results of Examples 1-11 and Comparative Examples 1-4 are summarized as follows:

[0165] like Figure 1As shown in Figure 1, in Comparative Example 1, the surface of the unmodified electrode was completely covered with bubbles after 5 minutes of power application, and high-intensity hydrogen evolution continued. In Example 1, hydrogen evolution was significantly suppressed by using the PAC-modified electrode. At 10 minutes, initial bubbles appeared locally on the electrode. During the entire reaction process, only a weak local hydrogen evolution reaction was maintained on the surface of the modified electrode. The experimental results show that electrode interface modification with PAC materials can significantly reduce the intensity of the hydrogen evolution reaction, showing a significant inhibitory effect on hydrogen evolution behavior.

[0166] like Figure 2 As shown, in Comparative Example 1, no PAC component group was added. When the electrode was energized for 5 minutes, the reaction interface was completely covered by the violent hydrogen evolution phenomenon, and high-intensity hydrogen evolution was maintained. In Example 2, in the experimental system containing 5 mg / L PAC additive, the evolution of hydrogen was effectively confined to the local area of the electrode, the amount of bubble generation was greatly reduced, and no continuous violent hydrogen evolution was observed. This inhibitory effect shows that the introduction of PAC significantly reduces the active site density and reaction rate of the hydrogen evolution reaction, showing a highly effective inhibitory effect on hydrogen evolution behavior.

[0167] like Figure 3 As shown, Comparative Example 1 begins to precipitate dense, tiny bubbles at the initial stage of the reaction (1 minute), and by 2 minutes, the entire reaction interface is covered by a large number of bubbles, followed by a continuous and intense hydrogen evolution process. In contrast, in Example 3, in the experimental system containing 5 g / L PAC additive, sporadic bubbles only appear at 2 minutes, and the subsequent hydrogen evolution process is significantly weaker than that of Comparative Example 1 in terms of both bubble generation and reaction intensity. These experimental results indicate that the addition of 5 g / L PAC can, to a certain extent, delay the progress of the hydrogen evolution reaction, reduce the intensity of hydrogen evolution, and have a positive effect on suppressing hydrogen evolution in this system.

[0168] As shown in Table 1, compared with the pure MFC electrolyte membrane without PAC in Comparative Example 2, the composite electrolyte membrane with 5% PAC added in Example 4 has significantly improved strength in the tensile test.

[0169] like Figure 4 As shown in the figure, the overall mechanical strength of the membrane samples shows that compared to the pure MFC electrolyte membrane without PAC in Comparative Example 2, the composite electrolyte membrane with 30% PAC in Example 5 shows significant improvements in both tensile and puncture strength. This demonstrates that the introduction of PAC effectively enhances the mechanical stability of the MFC-based electrolyte membrane, giving the composite membrane material improved resistance to dendrite puncture.

[0170] like Figure 5 As shown in the figure, the Zn / / PANI@CNT full cell in Example 5 has a rate performance of 0.5 to 4.0 A·g -1Under a series of surface current densities, its average discharge capacity is significantly better than that of Comparative Example 2 and is more stable, which shows that the introduction of PAC components effectively enhances the electrochemical properties of the MFC-based electrolyte membrane.

[0171] like Figure 6 As shown, the Zn||Zn symmetrical cell using the MFC-30% PAC-CA composite quasi-solid electrolyte membrane in Example 6 showed significant improvement in dendrite growth on the electrode surface, resulting in a uniform and flat surface with minimal pitting. In contrast, the unmodified pure MFC electrolyte membrane in Comparative Example 2 exhibited coarse dendrites and severe corrosion on the corresponding electrode surface. Therefore, the PAC component can effectively control dendrite growth and inhibit electrode corrosion.

[0172] like Figure 7 As shown, the Zn||Zn symmetric battery using the MFC-30% PAC-CA composite electrolyte membrane in Example 6 achieved a cycle life of over 550 hours with an extremely low overpotential. In contrast, the Zn||Zn symmetric battery using the pure MFC electrolyte membrane in Comparative Example 2 exhibited unstable cycling, a higher overpotential, and a significantly lower lifespan than that of Example 6. This demonstrates that the PAC component can homogenize the ion flow in the electrolyte, extend the cycle life of aqueous zinc-ion batteries, and optimize the overall stability of the battery.

[0173] like Figure 8 As shown in the figures, the zinc ion migration number of the Zn||Zn symmetric battery in Example 6 reached 63.8%, compared with 32.3% in Comparative Example 2, indicating that the PAC component in the cellulose-based composite electrolyte membrane sample can significantly regulate the ion flux in the aqueous zinc ion battery electrolyte and optimize the battery performance.

[0174] like Figure 9 As shown, from the perspective of the overall mechanical strength of the membrane sample, compared with the glass fiber membrane without PAC in Comparative Example 3, the 5 g / L PAC-modified glass fiber membrane in Example 7 has obvious improvements in tensile modulus and puncture strength, which is beneficial to improving its anti-dendritic puncture ability.

[0175] like Figure 10 As shown, compared with the glass fiber membrane without adding PAC in Comparative Example 3, the 1 g / L PAC+GA modified glass fiber membrane in Example 8 has significantly improved strength in the puncture test, which is beneficial to improving its anti-dendritic puncture ability.

[0176] like Figure 11 As shown, compared with the glass fiber separator without adding PAC in Comparative Example 3, the 20 g / L PAC+GA modified glass fiber separator in Example 9 has significantly improved strength in the puncture test.

[0177] like Figure 12 As shown, the Zn||Zn symmetric cells assembled with the glass fiber separator modified with 5g / L PAC in Example 7 and the glass fiber separator modified with 5g / L PAC+GA in Example 10 respectively showed high Zn||Zn symmetric cells at 1, 2, 4, 6, 8 and 10 mA·cm -2 In contrast, Comparative Example 3 quickly short-circuited during the rate test and had difficulty maintaining stable cycling, indicating that the PAC component can significantly extend the cycle life of aqueous zinc-ion batteries and optimize battery performance.

[0178] like Figure 13 As shown in Example 11, the cellulose membrane modified with 5 g / L PAC+GA was used to assemble the Zn||Zn symmetric battery. -2 The PAC component maintains good cycling stability at a surface current density of 100 nm, with a cycle life of over 500 h. In contrast, Comparative Example 4 quickly short-circuited during the test and had difficulty maintaining stable cycling, indicating that the PAC component can significantly extend the cycle life of aqueous zinc-ion batteries and optimize battery performance.

[0179] Table 1 Tensile strength of Example 4 and Comparative Example 2

[0180]

[0181] In summary, the multi-effect functional material (PAC) selected by the present invention effectively overcomes the drawbacks of traditional electrolytes in terms of modification methods and functional utility. While ensuring low cost and high performance, this material can significantly improve the performance of aqueous zinc ion batteries in various scenarios and realize multifunctional applications. A series of aqueous zinc ion battery optimized electrodes, electrolyte additives, composite electrolytes (simple composite or cross-linked composite) and modified diaphragms (simple composite or cross-linked composite) prepared based on this material are expected to provide support for the wide application of aqueous zinc ion batteries in industrial production, practical applications and daily life.

[0182] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. It is apparent to those skilled in the art that various changes, modifications, substitutions, and variations of these embodiments may be made without departing from the principles and spirit of the present invention, and the changes still fall within the scope of protection of the present invention.

Claims

1. Application of polyanionic cellulose in aqueous zinc ion batteries, characterized in that: The application methods include at least one of negative electrode interface modification, electrolyte additives, and diaphragm modification.

2. An aqueous zinc ion battery, characterized in that The aqueous zinc ion battery comprises a positive electrode, a negative electrode and an aqueous zinc ion solid or quasi-solid electrolyte, wherein the aqueous zinc ion solid or quasi-solid electrolyte is a solid or quasi-solid composite electrolyte containing polyanionic cellulose.

3. An aqueous zinc ion battery according to claim 2, characterized in that, The aqueous zinc ion solid or quasi-solid electrolyte is a composite electrolyte prepared by compounding polyanionic cellulose with a solid or quasi-solid electrolyte matrix; specific compounding methods include simple compounding and cross-linking compounding; among them, simple compounding refers to the direct physical compounding of polyanionic cellulose and the electrolyte matrix without chemical reaction during the process, and specific processes include surface coating, solution casting, electrospinning, impregnation or self-assembly; cross-linking compounding is to cause a cross-linking chemical reaction between the polyanionic cellulose and the cross-linking agent or the electrolyte matrix.

4. An aqueous zinc ion battery according to claim 3, characterized in that: The proportion of polyanionic cellulose in the solid or quasi-solid composite electrolyte is 1-50 wt%.

5. An aqueous zinc ion battery, characterized in that The aqueous zinc ion battery comprises a positive electrode, a negative electrode, a diaphragm and an aqueous zinc ion electrolyte, wherein the diaphragm is a polyanionic cellulose modified diaphragm.

6. An aqueous zinc ion battery according to claim 5, characterized in that: The preparation method of the polyanionic cellulose modified diaphragm is as follows: dissolving the polyanionic cellulose in water to prepare a modified solution, or dissolving the polyanionic cellulose and a cross-linking agent in water to prepare a modified solution; then using the obtained modified solution to soak, spray, self-assemble or surface-coat the diaphragm, and then drying it.

7. An aqueous zinc ion battery according to claim 6, characterized in that: The concentration of the polyanionic cellulose in the modified solution is 0.1-30 g / L.

8. An aqueous zinc ion battery, characterized in that The aqueous zinc ion battery comprises a positive electrode, a negative electrode, a diaphragm and an aqueous zinc ion electrolyte, wherein the aqueous zinc ion electrolyte is a zinc ion electrolyte containing polyanionic cellulose as an additive.

9. An aqueous zinc ion battery according to claim 8, characterized in that: The concentration of polyanionic cellulose in the zinc ion electrolyte is 0.005-5g / L.

10. An aqueous zinc ion battery, characterized in that: The aqueous zinc ion battery comprises a positive electrode, a negative electrode, a separator and an aqueous zinc ion electrolyte, wherein the negative electrode is a polyanionic cellulose modified electrode.

11. An aqueous zinc ion battery according to claim 10, characterized in that: The preparation method of the polyanionic cellulose modified electrode is: constructing a polyanionic cellulose modification layer on the surface of the zinc negative electrode by surface coating, electrostatic adsorption, self-assembly, spraying, electrophoresis or electrochemical deposition.